Analisis Kesenjangan Digital Tingkat Pertama dan Daya Beli Komunikasi Kelas Sosial di Desa Semplak Barat Kabupaten Bogor - Anugrah , Gilang Tresna Putra; Sjaf , Sofyan; Hermansah , Tantan (Journal of Industrial Engineering & Management Research, 2023)
The digital divide, as a result of the development of the digital age and the 4.0 industrial revolution, has become an important issue even at the international level. Ragnedda attributes the digital divide to an individual’s social class as a preceding factor. This article aims to analyze the first-order digital divide that occurs in each social class, as well as consider the purchasing power of communication in West Semplak Village. The method used in writing this article is through secondary data analysis using information contained in the Data Desa Presisi (DDP). The results of this study confirm that: (1) There is a difference in the first-level digital divide, where the order is the middle class with a percentage of 10.00%, followed by the lower class with 7.10%, and the upper class with 1.91%; (2) Judging from the average value of communication costs, the upper class has a cost of Rp232,719, which is greater than the class below; (3) When considering the proportion of communication costs to income in each class, the order of the proportion of communication purchasing power from the largest is the lower class at 9.39%, followed by the middle class with 6.44%, and the upper class with 6.07%.